A STUDY ON CONSUMER AWARENESS OF GREEN MARKETING IN CHENNAI CITY (International Journal of Food and Nutritional Sciences, 2022)
In today’s environmentally conscious world the word “Green” has become a buzz word.Environmental issue is a main concern nowadays as almost every country’s government andsociety has started to be more aware about these issues. This paper will be discussing thecustomer’s awareness and knowledge towards green marketing and green products. The customer’sattitude towards buying green products also studied. For the purpose of study convenient samplingsurvey will be carrying out among 100 respondents in Chennai city with the help of questionnaire.